2015
DOI: 10.4103/0976-5042.173962
|View full text |Cite
|
Sign up to set email alerts
|

Post-ERCP pancreatitis and its related factors: A prospective study in Cipto Mangunkusumo National General Hospital

Abstract: Objectives: Endoscopic retrograde cholangiopancreatography (ERCP) is a widely used procedure for the diagnosis and treatment of pancreatobiliary disease with post-ERCP pancreatitis (PEP) is the most common complication. The goal of this study was to comprehensively evaluate the potential patient- and procedure-related risk factors for PEP. Methods: A 25-variable database was compiled from information collected before, during, and 24-72 h after ERCP for 238 patients who underwent diagnostic or therapeutic ERCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In addition, the percentage of deaths occurring as a consequence of any complication of ERCP has been reported to be 0.33% [ 5 , 6 ]. A higher rate of PEP of 26.5% was reported in a prospective study conducted in our hospital [ 7 ]. ERCP is reserved exclusively for therapeutic purposes because of the risks, and EUS and MRCP have become the modalities of choice for diagnosing choledocholithiasis [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 65%
“…In addition, the percentage of deaths occurring as a consequence of any complication of ERCP has been reported to be 0.33% [ 5 , 6 ]. A higher rate of PEP of 26.5% was reported in a prospective study conducted in our hospital [ 7 ]. ERCP is reserved exclusively for therapeutic purposes because of the risks, and EUS and MRCP have become the modalities of choice for diagnosing choledocholithiasis [ 1 - 3 ].…”
Section: Introductionmentioning
confidence: 65%
“…Other studies from the various country also found male predominance. [15][16][17] Regarding the indications of ERCP, choledocholithiasis was the most common indication found in nearly half of the study subjects, followed by Cholangiocarcinoma, periampullary carcinoma, and carcinoma head of the pancreas. A prospective study also found the highest cases of choledocholithiasis (32%) as an indication of ERCP, whereas cholangiocarcinoma and carcinoma head of pancreas as the second-highest indications.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 238 subjects in Indonesia reported PEP to occur in 63 (26%) cases. [ 17 ] Another study in Ohio, USA, found 23% PEP. [ 18 ] Another recent study on 300 cases reported 11.7% of PEP.…”
Section: Discussionmentioning
confidence: 99%